EFEKTIVITAS PENEGAKAN HUKUM TERHADAP PEMBAKARAN HUTAN DAN LAHAN DI KALIMANTAN TENGAH - Pratomo Beritno (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2019)
Indonesia is a tropical country that has the threat of forest destruction, both due to illegal logging and burning of land that can cause permanent forest destruction. Central Kalimantan is a province that is prone to land and forest fires every year. Plantation land development such as palm oil and acacia are the dominant causes of forest and land fires that occur in Central Kalimantan. Extensive land and forest fires in Central Kalimantan occur because of human fires. The purpose of forest and land burning is for the economic benefit of the perpetrators of the burning. The impact of burning land and forests in the Central Kalimantan region, the community suffered loss of health problems, economic losses, disrupted transportation, and damage to wildlife habitat. The government has strictly regulated the prohibition of land and forest fires, but land and forest fires are still being carried out on purpose, so it is necessary to examine the effectiveness of law enforcement on forest and land burning in Central Kalimantan. The effectiveness of law enforcement on forest and land burning in Central Kalimantan has not been effective. This happens because there are still communities and companies that burn forests and land. Law enforcement factors, and community factors are obstacles to the ineffectiveness of law enforcement against forest and land burning in Central Kalimantan. For the rule of law to be effective, the law must be clear, law enforcers carry out their duties and functions, as well as direct action against perpetrators of land and forest fires. The effectiveness of law enforcement on forest and land burning in Central Kalimantan will be achieved if the government and law enforcement officials strictly enforce legal sanctions against perpetrators of land and forest fires in the form of administrative sanctions for forest fires in the form of, freezing of environmental permits, and or revocation of environmental permits, the responsibility for recovery and criminal responsibility of the person responsible for the business and / or activity must pay compensation and / or take certain actions. Add and threaten severe penalties for perpetrators of forest and land burning. Increasing the awareness that exists in each individual and group of the importance of obeying a rule for the common good.